PROFIL PENGGUNAAN OBAT ANTIHIPERTENSI DI PUSKESMAS JENAWI KARANGANYAR TAHUN 2018 - Rahmadhani Tyas Angganawati; Esti Nafiroh; Umi Nafisah; Riyan Setiyanto (Program Studi D3 Farmasi Politeknik Indonusa Surakarta, 2021)
Hypertension is a condition where systolic value >140 mmHg and diastolic blood pressure >90 mmHg. Hypertension is one of the main causes of death. This study aims to determine the profile of the use of antihypertensive drugs in Jenawi Karanganyar Health Center in 2018. The research method used is descriptive retrospective data. The research subjects were selected using a Porposive Sampling technique that met the inclusion criteria as follows patients diagnosed with hypertension, patients with health insurance, over 18 years of age and had complete medical record data. The results of a study of 300 medical records of hypertension sufferers showed 66,7% women and 33,3% men, based on age 18-25 years 0%, 26-35 years 1,7%; 36-45 years 7%, 46-55 in 21,6%; 56-65 years 26%, more than 65 years 43,7%. The drug use was most often given singly as much as 97,6%; the group of drugs most widely used was Calcium Channel Blockers (CCB) 82,4%; and the most used drug item Amlodipin was 50,5%. Research is expected to be a reference in the management of antihypertensive drugs at the Karanganyar Jenawi Health Center, namely the planning and procurement of drugs according to the National Formulary standards.